Comparability of Limitation, Deprivation and Termination of Parental Responsibility in Kosovo and in Some Balkans States - Tahiri, Burim (European Journal of Multidisciplinary Studies, 2016)
The parental right shall regulate the relationships between parents and children as well as other persons of kin. The characteristics of this right shall be the various elements which are very important in accomplishment of relations between parents and children. In this paper we will be focused on limitation, deprivation and termination of parental responsibility. Even that the importance of elements comprising the parental responsibility is undisputed, our focus has derived as a consequence of the importance and sensitivity that these elements have in contrary to the other elements comprising the parental right. Limitation of the parental responsibility comes due to the abuse of children by their parents. In such cases the parents shall be limited to parental responsibility to that time limit such a situation lasts. Deprivation of parental responsibility may come as a consequence of parents, behaviors from which the personality or property of the children is at a high danger. Parents with such behaviors that endanger seriously the personality or property of children shall be deprived from the parental responsibility. Termination of parental responsibility happens in certain cases based on which the parents shall not be any more responsible for their children after there have been fulfilled the conditions foreseen by the Law. With the positive legislations of some countries included in this paper there have been determined expressively the cases of termination of parental responsibility. It is important to mention that not all countries have determined, in their Laws, the matter of termination of parental responsibility that makes the discussion of this paper more distinctive.
Keywords: Parental responsibility, right, parent, child, limitation, deprivation, termination